Efeito de um inibidor dual da enzima fosfatidilinositol-3-quinase (PI3K) e do alvo da rapamicina em mamíferos (mTOR) nas alterações patológicas induzidas por peptídeo β-amilóide 1-42 in vivo e in vitro - Paula Maria Quaglio Bellozi (2014)
Introduction: Alzheimer’s Disease (AD) is a neurodegenerative disease, which is the main cause of dementia. Its main symptom is the cognitive deficit, specially memory loss and learning disability, and the current therapy do not stop disease progression. There is neuronal death, neuroinflammation and changes in neurotrophins production in AD. The PI3K/ Akt/ mTOR pathway is involved in cellular metabolism, growth and survival, and it seems to be overactivated in AD. Therefore, the aim of the present study is to investigate the effects of the treatment with a dual PI3K and mTOR inhibitor, NVP-BEZ235, in a murine model of AD and hippocampal neuronal cultures stimulated with amyloid-β. . Methods: Male C57Bl/6 mice were submitted to perform stereotactic surgery to intra-hippocampal injection of 400 pmol of amyloid-β 1-42 in a volume of 0.5 l or PBS. Animals were treated 8 days with NVP-BEZ235 25 mg/Kg, rivastigmine 0,3 mg/Kg or their vehicles, and then submitted to object recognition task. Following that, animals were submitted to intracardiac perfusion in order to obtain hippocampal cerebral slices, or their cerebral tissues were removed. The slices were stained with NISSL, to access cellular viability, or Fluoro-Jade C to access neuronal death. The hippocampus were processed in order to measure neurotrophic factors BDNF and NGF levels, as well as inflammatory mediators IL-1β IL-2, IL-4, IL-6, IL-10, TNF-α, IFN-γ and IL-17A levels. In in vitro experiments, hippocampal neuronal cultures were prepared from newborn C57Bl/6 mice. Amyloid β or its vehicle were added to the cultures and the treatment was done with memantine or NVP-BEZ235 20 or 100 µM, to access the neuronal death assay. Statistical analysis were performed using GraphPad Prism 5 and expressed as mean ± SEM (P<0,05). Results: Mice that received amyloid-β revealed memory loss,significantly reversed with NVP-BEZ235. There was a tendency of neuronal death increase in CA1, dentate gyrus and CA3 of hippocampus in animals receiving amyloid-β, which was reversed with the PI3K and mTOR inhibitor. In cultures, there was a neuronal death following treatment with amyloid-β, which was also significantly prevented with memantine and NVP-BEZ235. No difference was observed in the levels of BDNF, NGF, IL-1β, IL-2, IL-4, IFN-γ and IL-17A in both ipsilateral and contralateral hippocampus. However, there was an increase in IL-6 (p=0,079) and TNF-α (p=0,056) levels in ipsilateral hippocampus of mice treated with NVP-BEZ235, as well a significant increase in IL-10. Conclusions: Amyloid-β induces cognitive changes and neuronal death in vitro, which can be reversed or prevented by NVP BEZ235 treatment. Furthermore, the drug seems to improve neuronal survival and change pro- and anti-inflammatory cytokines levels. Thus, the mechanism by which the drug improves cognitive parameters might be related to neuronal death decrease and changes in the production of cytokines involved in memory.